Grenzüberschreitende Infrastrukturplanung in Europa. Die "anderen" Ergebnisse der van Miert-Kommission. - Fabian, Thomas (Deutscher Verkehrs-Verl., 2005)
In Ergänzung zum Beitrag "Karel van Miert und der frische Wind in der europäischen Infrastrukturpolitik" von H. Nowak (Internationales Verkehrswesen, Heft 7+8/2004, S.304-306) werden in dem Beitrag die "anderen" Empfehlungen der van Miert-Gruppe dargestellt, die unter dem Stichwort Netzmanagement und Koordinierung zusammengefasst wurden. difu

The numerous proposals made by the High Level group chaired by Karel van Miert were - inter alia - intended to identify organisational and structural obstacles in the implementation process of TEN-transport infrastructure projects. Cross-border sections of these projects have proved to be the most challenging investments and will therefore most likely to profit from initiatives to speed them up. The idea of appointing a "European Coordinator" for these sections derives from the positive experiences that have been made with the more formal and (to some extent) institutionalised structures with the Pan-European Transport Corridors. Applying these experiences to the development of the TEN-transport might not only ease their development. In the long run the van Miert proposals and their subsequent implementation in legal regulations might easily transform European transport infrastructure planning and policy. difu
Keywords: Verkehr; Verkehrsweg; Eisenbahn; Straße; Verkehrsinfrastruktur; Verkehrsplanung; Grenzüberschreitender Verkehr; Transeuropäisches Verkehrsnetz